Factors Associated with Human Papillomavirus Vaccination Among Diverse Adolescents in a Region with Low Human Papillomavirus Vaccination Rates - Kepka, Deanna (Health Equity, 2018)
Introduction: This study assesses the sociodemographic facilitators and barriers to human papillomavirus (HPV) vaccination for diverse teens in a region with low HPV vaccination rates. Materials and Methods: In this community-based participatory research study, we surveyed adult family members of teens aged 11–17 years from African American, African refugee, American Indian/Alaskan Native, Hispanic/Latino, and Native Hawaiian/Pacific Islander community groups in Salt Lake City, Utah. Bivariate analyses assessed associations between sociodemographic characteristics and, respectively, HPV vaccine receipt and intentions for vaccination. Barriers to vaccination were also investigated. Results: Only 20% of participants had vaccinated at least one of their children with at least one dose of the HPV vaccine. HPV vaccination was significantly related to caregiver age (p=0.035), race/ethnicity (p=0.001), educational attainment (p=0.006), annual household income (p=0.0454), years in the United States (p=0.023), and caregiver parent birthplace (p=0.008). Among caregivers with unvaccinated children, intention to vaccinate was significantly related to race/ethnicity (p=0.048 for daughters; p=0.003 for sons), caregiver parent birthplace (p=0.023 for sons), health insurance coverage (p=0.028 for daughters; p=0.047 for sons), and type of health insurance coverage (p=0.008 for sons). The most frequently cited barriers to HPV vaccination were lack of knowledge about the HPV vaccine, costs, side effects, and child not being sexually active. Conclusions: Our results show substantially lower HPV vaccine coverage than both national and state rates, signaling the urgent need for multipronged HPV vaccination interventions within these communities; strategies are discussed.